Left Ventricular Ejection Fraction Evaluation Using SPECT Images - Musa, Mahmoud A. A.; Zobly, Sulieman M. S.; Ahmed, Mawahib G. A. (Gezira Journal of Engineering and Applied Sciences, 2026)
Cardiovascular diseases represent a major global health burden. In Sudan, the incidence has increased in recent years, partly due to diagnostic inaccuracies in cardiac imaging and the high cost of commercial image processing software. Accurate quantification of left ventricular ejection fraction (LVEF) is essential for cardiac function assessment. This study aimed to develop and validate a low-cost MATLAB-based algorithm for automated LVEF calculation from Gated Single Photon Emission Computed Tomography (Gated SPECT) images. Twelve cardiac patients underwent Gated SPECT imaging. A custom MATLAB toolbox was developed to perform left ventricular segmentation, detect end-diastolic (EDC) and end-systolic counts (ESC), and calculate LVEF. Algorithm performance was evaluated by comparing calculated LVEF with reference values and assessing diagnostic accuracy. Among the 12 patients, 5 exhibited normal cardiac function with LVEF values of 60.4%, 55.8%, 53.4%, 56.3%, and 59.1%, with 97% accuracy relative to reference software. Seven patients showed impaired function with LVEF values of 38.5%, 34.5%, 25.3%, 36.1%, 18.8%, 20.0%, and 40.7%. Correlation analysis yielded r = 0.80. The proposed MATLAB algorithm provides accurate, accessible, and reproducible LVEF quantification from Gated SPECT images, offering a viable alternative to expensive commercial software. The researcher recommends integrating this method into routine SPECT analysis in resource-limited settings and validating it on larger cohorts.